Optical Polarization Sensor Based on a Metalens - Victor Kotlyar; Anton Nalimov; Alexey Kovalev; Sergey Stafeev (Sensors, 2022)
We investigated an optical microsensor of the polarization state of a laser light based on a metalens. In contrast to known polarization sensors based on metasurfaces that deflect different polarization types using various angles to the optical axis, the studied polarization sensor generated different patterns in the metalens focus to realize varied polarization states: left circular polarization generated a light ring in the focus, right circular polarization generated a circular focal spot, and linear polarization generated an elliptic spot with two sidelobes. Moreover, the tilt angle of the linear polarization matched the tilt angle of the elliptic focal spot. The simulation results were consistent with the theoretical predictions. A metalens with a diameter of several tens of microns was designed and fabricated in a thin amorphous silicon film with a thickness of 120 μm and a low aspect ratio, high numerical aperture, and short focal distance equal to a wavelength of 633 nm.